Prevalence and Factors Associated with Overweight/Obesity in Adolescent School Girls: A Cross-Sectional Study in Kolkata, India - Roy, Papiya; Chakrabarty, Suman; Chatterjee, Diptendu; Bharati, Premananda (Anthropological Review, 2022)
Overweight and obesity in adolescent girls are considered a leading global public health issues in recent times. There is a need to evaluate the potential socioeconomic and behavioural factors behind adolescents’ overweight and obesity in different environmental settings. The present study aims to understand the prevalence of overweight and obesity among urban adolescent school girls and to determine the association between selected socioeconomic and behavioural factors and overweight/obesity. This is a cross-sectional study using a multistage stratified cluster sampling with a sample size of 1041 adolescent girls aged 10 to 18 years from schools of Kolkata, India. Overall prevalence of overweight and obesity were 18.9% and 23.7%, respectively. The prevalence of overweight and obesity was higher among those adolescent girls whose parents had completed higher education (49.5%) and had higher monthly per capita household expenditure (48.4%). Stepwise binary logistic regression analysis confirmed that the probability of being overweight/ obese tended to be in adolescents who slept less than 7 hours per day (p<0.001). Overweight /obesity was also higher among those children whose fathers were fatty (p=0.002), taken medicines three months before the survey (p=0.008), and watched television and mobile phones for more than 1 hour a day (p=0.039). Rapid change in modern lifestyles is seemingly decreasing sleep duration in adolescents with subsequent negative impact on their health.